Invasive pneumococcal disease in relation to vaccine type serotypes - Paeton L. Wantuch; Fikri Y. Avci (Taylor & Francis Group, 2019)
Since 1983 the world has been introduced to four vaccines combating disease caused by Streptococcus pneumoniae bacteria. However, despite vaccination programs disease caused by S. pneumoniae continues to lead to high morbidity and mortality worldwide. Surprisingly, instances of invasive pneumococcal disease (IPD) are still highly attributed to serotypes found in the current vaccine, such as serotypes 3 and 19A. Conversely, non-conjugate vaccine serotypes, such as 35B, are increasing and of rising interest. The persistence of vaccine type serotypes and the increase in non-conjugate vaccine type serotypes show the need for further research into conjugate vaccine design and the need for novel strategies to combat IPD. Abbreviation: IPD: invasive pneumococcal disease